East Asian warm season temperature variations over the past two millennia - Zhang, Huan; Werner, Johannes P.; Garcia-Bustamante, Elena; Gonzalez-Rouco, Fidel; Wagner, Sebastian; Zorita, Eduardo; Fraedrich, Klaus; Jungclaus, Johann H.; Ljungqvist, Fredrik Charpentier; Zhu, Xiuhua; Xoplaki, Elena; Chen, Fahu; et al. (My University, 2018)
East Asia has experienced strong warming since the 1960s accompanied by an increased frequency of heat waves and shrinking glaciers over the Tibetan Plateau and the Tien Shan. Here, we place the recent warmth in a long-term perspective by presenting a new spatially resolved warm-season (May-September) temperature reconstruction for the period 1â 2000 CE using 59 multiproxy records from a wide range of EastÂ Asian regions. Our Bayesian Hierarchical Model (BHM) based reconstructions generally agree with earlier shorter regional temperature reconstructions but are more stable due to additional temperature sensitive proxies. We find a rather warm period during the first two centuries CE, followed by a multi-century long cooling period and again a warm interval covering the 900-1200 CE period (Medieval Climate Anomaly, MCA). The interval from 1450 to 1850 CE (Little Ice Age, LIA) was characterized by cooler conditions and the last 150 years are characterized by a continuous warming until recent times. Our results also suggest that the 1990s were likely the warmest decade in at least 1200 years. The comparison between an ensemble of climate model simulations and our summer reconstructions since 850 CE shows good agreement and an important role of internal variability and external forcing on multi-decadal time-scales.
Keywords: ddc:910